2022
DOI: 10.3389/fvets.2022.979548
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica frequency in backyard chickens in Vermont and biosecurity knowledge and practices of owners

Abstract: The popularity of backyard chickens has been growing steadily over the past 10 years, with Covid-19 stay at home orders in 2020 yielding an added boost in popularity. Concurrently, cases of salmonellosis from live poultry exposure have also risen. Previous research on backyard chicken owners has focused primarily on urban chicken owners, which may have differing knowledge and biosecurity habits from rural backyard chicken owners. The goal of this study was to investigate the prevalence of S. enterica in rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Larsen et al ( 75 ) suggested that there is a need in improving messaging on biosecurity and risks due to the increase in unsafe practises despite the increase in messaging about infection risks and good biosecurity while Damiaans et al ( 76 ) and Higgins et al ( 77 ) suggested that farmers ignore practising on-farm biosecurity due to a lack of biosecurity information. However, this is likely not the case in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Larsen et al ( 75 ) suggested that there is a need in improving messaging on biosecurity and risks due to the increase in unsafe practises despite the increase in messaging about infection risks and good biosecurity while Damiaans et al ( 76 ) and Higgins et al ( 77 ) suggested that farmers ignore practising on-farm biosecurity due to a lack of biosecurity information. However, this is likely not the case in this study.…”
Section: Discussionmentioning
confidence: 99%
“…While we found little evidence on the extent of backyard poultry production shifts and who participated, expansions in backyard poultry production have quickly given way to concerns about disease transmission for new producers. In Vermont, production of backyard chickens was most common in rural areas and among wealthier and more educated households ( 37 ). Larsen et al, also showed low uptake of biosecurity practices among backyard poultry rearers, and that nearly 20% of backyard flocks have Salmonella enterica .…”
Section: Introductionmentioning
confidence: 99%